THE ROLE OF COMMUNITY HEALTH CENTRES (PUSKESMAS) IN THE IMPLEMENTATION OF SEXUAL VIOLENCE PREVENTION FOR SCHOOL-AGE CHILDREN IN ELEMENTARY SCHOOLS - T Kartilah; sofia februanti; B Sakti; U A Hidayat (Journal of Maternity Care and Reproductive Health, 2018)
The number of events of sexual violence among school-age children in Indonesia is still high. Community health centres (puskesmas) have established school health centres (UKS). However, the methods implemented by the community health centres for preventing sexual violence among school-age children have not been identified, including primary, secondary, and tertiary preventions. This research aims to examine the prevention practices of sexual violence among school-age children conducted by community health centres. It employs qualitative method. The roles of community health centres in Tasikmalaya and Bandung in implementing the practices of sexual violence were identified through the school health centres (UKS) program. The findings indicate that in the primary prevention, the community health centres do not have specific programs; they perceived the sexual violence prevention as not being part of their responsibility. In terms of secondary prevention, the community health centres do not have the authority to monitor students’ actions; the community health centres take actions based on schools’ reports. In the tertiary prevention, the community health centres only provide health examinations for identifying sexual violence. Generally, the community health centres have not played specific roles in the primary, secondary, and tertiary prevention of sexual violence among school-age children.Keywords: school-age children, sexual violence